Canadian Normal Lung Function Values - Nick R Anthonisen (Canadian Respiratory Journal)
In this issue of the Canadian Respiratory Journal, Gutierrez et al (pages 414-424) present normal lung function values and prediction equations for white Canadians. They had six laboratories across the country each test approximately 100 volunteer, nonsmoking white adults (the target was 120 each), with appropriate variation in age and sex. Adequate representation of different ages and sex were obtained, although it appeared to be harder to recruit elderly men than elderly women. A full battery of tests was performed on each person. The equipment was not standardized and varied from centre to centre, and some centres performed slightly different tests than others; in other words, the study was done under field conditions. The results were analyzed for each centre and pooled to produce the Canadian model. This was compared with several similar models developed in Europe and the United States (1-5).